2021
DOI: 10.19128/turje.811919
|View full text |Cite
|
Sign up to set email alerts
|

Ethical leadership in educational organizations: A cross-cultural study

Abstract: The goal of this study is to examine how educators from both Eastern and Western cultures define ethical leadership and which characteristics they associate with ethical leaders. This study also explores ethical examples of educators, tries to answer if major events like Covid-19, high-technology, migration have changed their ethical perceptions, and lastly, examines their reactions to unethical conduct. This qualitative study employed a phenomenological research design. Data collection using semi-structured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Corruption undermines human rights, such as the right to equality and freedom of trade and occupation (Göçen, 2021). When people pay bribes to get things that they are not entitled to, like old age pensions or other forms of social grants, there is less money available for people who really need it (Sebola et al, 2014).…”
Section: The Impact and Costs Of Corruption In South Africamentioning
confidence: 99%
See 3 more Smart Citations
“…Corruption undermines human rights, such as the right to equality and freedom of trade and occupation (Göçen, 2021). When people pay bribes to get things that they are not entitled to, like old age pensions or other forms of social grants, there is less money available for people who really need it (Sebola et al, 2014).…”
Section: The Impact and Costs Of Corruption In South Africamentioning
confidence: 99%
“…The costs of corruption are particularly high for countries in great need of inflows of productive foreign capital (Göçen, 2021). Widespread corruption provides a poor environment that does not attract foreign investment, and those investors are likely to make long-term contributions to development (Mudau & Madzivhandila, 2022).…”
Section: Reduction In Productive Investment and Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethical leaders' norms and expectations in Eastern societies are different from the Western perspective, as they are rooted in the spiritual aspects of everyday life. Therefore, it is suggested that the global view of ethical leadership derived from specific cultural values and practices should be explored (Resick et al, 2011;Göçen, 2021). Forsyth et al (2008) conducted a meta-analysis of more than 80 studies based on relativism and absolutism/idealism.…”
Section: Introductionmentioning
confidence: 99%